2014
DOI: 10.1038/srep06903
|View full text |Cite
|
Sign up to set email alerts
|

Designer self-assembling hydrogel scaffolds can impact skin cell proliferation and migration

Abstract: There is a need to develop economical, efficient and widely available therapeutic approaches to enhance the rate of skin wound healing. The optimal outcome of wound healing is restoration to the pre-wound quality of health. In this study we investigate the cellular response to biological stimuli using functionalized nanofibers from the self-assembling peptide, RADA16. We demonstrate that adding different functional motifs to the RADA16 base peptide can influence the rate of proliferation and migration of kerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(57 citation statements)
references
References 42 publications
1
56
0
Order By: Relevance
“…(a)]. The inclusion of proteins/peptides like KLD‐12 and Arg‐Gly‐Asp (RGD) peptides to the synthetic scaffolds improves the biocompatibility and infiltration of the cells by providing the necessary functional groups and surface hydrophilicity . The increase in the porosity helps the cells to penetrate through the scaffolds and efficiently utilize the nutrients for its growth.…”
Section: Discussionmentioning
confidence: 99%
“…(a)]. The inclusion of proteins/peptides like KLD‐12 and Arg‐Gly‐Asp (RGD) peptides to the synthetic scaffolds improves the biocompatibility and infiltration of the cells by providing the necessary functional groups and surface hydrophilicity . The increase in the porosity helps the cells to penetrate through the scaffolds and efficiently utilize the nutrients for its growth.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, bilayer hydrogel scaffolds (either in combination with a fibrous mat or porous scaffold) have also been reported for effective drug delivery to enhance wound healing and to improve skin regeneration via seeding of stem cells derived from debrided human burn skin [157,158]. More recently, self-assembling peptide-based hydrogel scaffolds have been reported to accelerate burn wound healing and skin cells proliferation [159,160] with brighter prospects for dermal tissue regeneration. …”
Section: Scaffolding Approaches and Different Types Of Scaffolds Imentioning
confidence: 99%
“…Recent studies have reported that functionalized SAP enhances angiogenesis, liver regeneration, skin cell proliferation, and the neural stem cell phenotype. [16][17][18][19] In a previous study, we found that SAP enhanced islet viability and function in vitro, 20 and identified functionalized SAP as a potential scaffold for islet transplantation.…”
mentioning
confidence: 90%